Drug Use Among Immigrant and Non‐immigrant Adolescents: Immigrant Paradox, Family and Peer Influences. (27th March 2015) - Cristini, Francesca; Scacchi, Luca; Perkins, Douglas D.; Bless, Kimberly D.; Vieno, Alessio
Abstract The present study compared immigrant and Italian native adolescents with regard to drug use. Additionally, we analysed the role of family and peer risk and protective factors for drug use. Participants included 2533 Italian native and immigrant adolescents (mean age = 17.19, SD = 1.6; 66.7% male). Results showed that immigrant adolescents reported lower levels of marijuana and pharmaceutical drug abuse than non‐immigrant adolescents. These results confirm the so‐called immigrant paradox phenomenon: the counterintuitive finding that although immigrants often live under challenging conditions and reported lower economic affluence compared with nationals, some health outcomes have not always corresponded to their relative disadvantage. Immigrant adolescents also reported higher level of parental control and lower levels of affiliation with deviant peers, but lower levels of child disclosure, parental solicitation and parental knowledge. Socio‐economic status and parental monitoring showed equivalent effects on drug use for immigrant and non‐immigrant adolescents. Results have implications for preventive interventions for immigrant adolescents and families, including the need to develop programmes that leverage the benefits of the immigrant paradox for immigrant communities. Future research should analyse the processes that lead to lower levels of drug use in immigrant adolescents and investigate the influence of friendship networks on immigrant adolescent drug use behaviour. Copyright © 2015 John Wiley & Sons, Ltd.